2012
DOI: 10.1016/j.npep.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pituitary adenylate cyclase-activating polypeptide on elevated plus maze behavior and hypothermia induced by morphine withdrawal

Abstract: The aim of the present investigation was to study the effects of pituitary adenylate cyclase-activating polypeptide (PACAP) on morphine withdrawal-induced behavioral changes and hypothermia in male CFLP mice. Elevated plus maze (EPM) and jump tests were used to assess naloxone-precipitated morphine withdrawal-induced behavior responses. Different doses of subcutaneous (s.c.) naloxone, (0.1 and 0.2 mg/kg, respectively) were used to precipitate the emotional and psychical aspects of withdrawal on EPM and 1 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(52 reference statements)
2
5
0
Order By: Relevance
“…In the current report, we showed that mice undergoing NAL‐precipitated MOR withdrawal exhibit an increase in the time spent and entries to the open‐arms of the EPM in accordance with previous studies (Hodgson et al, ; Hofford et al, ; Lipták et al, ). The interpretation of these results is quite controversial but, a recent report by Lipták et al, () has shown that mice undergoing NAL‐precipitated MOR withdrawal spent significantly more time and traveled significantly more distance in the center of the open field compared to the control mice confirming the results observed in the EPM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current report, we showed that mice undergoing NAL‐precipitated MOR withdrawal exhibit an increase in the time spent and entries to the open‐arms of the EPM in accordance with previous studies (Hodgson et al, ; Hofford et al, ; Lipták et al, ). The interpretation of these results is quite controversial but, a recent report by Lipták et al, () has shown that mice undergoing NAL‐precipitated MOR withdrawal spent significantly more time and traveled significantly more distance in the center of the open field compared to the control mice confirming the results observed in the EPM.…”
Section: Discussionsupporting
confidence: 93%
“…mice develop a MOR dependence without altering its behavior (Diaz et al, ). The dependence state did not modify EPM behaviors for either sex in accordance with previous reports (Lipták et al, ; Zhang and Schulteis, ). We used NAL (6 mg/kg, i.p.)…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, circadian genes, such as Per3 , which was changed in morphine-exposed male mice, have been associated with opioid-induced hyperalgesia in mice ( Zhang et al, 2019 ) and mutations in PER3 are associated with opioid dependence in humans ( Surovtseva et al, 2012 ). Other genes that were upregulated in morphine-exposed males include the PACAP1 receptor and ryanodine receptors, which are also associated with opioid withdrawal ( Ohsawa and Kamei, 1999 ; Mácsai et al, 2002 ; Martin et al, 2003 ; Lipták et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…While changes in body temperature have not been well characterized in rodent models of NOWS, a 2019 study showed that body temperature decreased following prenatal opioid exposure (Wallin et al, 2019). Additionally, studies in adult rodent models of opioid withdrawal have also reported a decrease in body temperature (Belknap, 1989;Lipt ak et al, 2012). In contrast to these previous reports, the body temperature of spiny mice pups from the morphine exposed groups was significantly higher in both sexes.…”
Section: Discussionmentioning
confidence: 94%